Social consequences and mental health outcomes of living in high-rise residential buildings and the influence of planning, urban design and architectural decisions: A systematic review. (October 2019) - Barros, Paula; Ng Fat, Linda; Garcia, Leandro M.T.; Slovic, Anne Dorothée; Thomopoulos, Nikolas; de Sá, Thiago Herick; Morais, Pedro; Mindell, Jennifer S.
Abstract: Different types of high-rise residential buildings have proliferated in different countries at least since the 1940s, for a range of reasons. This paper aims to provide an overview of the current state of evidence on how planning, urban design and architectural aspects of high-rise residential buildings may influence social well-being and mental health. A systematic review following the PRISMA guidelines was conducted. Searches for peer-reviewed papers were conducted in MEDLINE, Embase, PsycInfo, Scopus, SciELO, and Web of Science; 4100 papers were assessed. 23 empirical studies published between 1971 and 2016 were included. The review found that house type, floor level, as well as spaces intrinsic to high-rise residential buildings (e.g. shared stairwells) are associated with social well-being and mental health. However, conceptual gaps and methodological inconsistencies still characterise most of the research in this field. We expect that research about and policy attention to this subject may intensify due to its strategic relevance in the face of global challenges such as increasing urbanization and loneliness. This paper concludes by highlighting a number of recommendations for future research. Highlights: House type, floor level, and spaces intrinsic to high-rises are associated with social well-being and mental health. Most research shows methodological problems and lack of conceptual consensus. Cross-national research and studies in cities in the Global South are needed. There is a lack of studies on positive mental health. Mediators, moderators and confounding variables need to be studied conjointly.